Elemental Composition at Silicone Hydrogel Contact Lens Surfaces. (November 2018) - Rex, Jessica; Knowles, Timothy; Zhao, Xueying; Lemp, Jessie; Maissa, Cecile; Perry, Scott S.
Abstract : Objectives: The outermost surface composition of 11 silicone hydrogel (SiHy) lenses was measured using X-ray photoelectron spectroscopy (XPS) to understand differences in wettability and potential interactions within an ocular environment. The SiHy lenses tested included balafilcon A, lotrafilcon A, lotrafilcon B, senofilcon A, comfilcon A, and somofilcon A reusable 2-week or monthly replacement lenses and delefilcon A, samfilcon A, narafilcon A, stenfilcon A, and somofilcon A daily disposable lenses. Methods: All lenses were soaked for 24 hr in phosphate-buffered saline to remove all packaging solution and dried under vacuum overnight before analysis. X-ray photoelectron spectroscopy measurements were performed at 2 take-off angles, 55° and 75°, to evaluate changes in elemental composition as a function of depth from the surface. Results: Detailed analysis of the XPS data revealed distinct differences in the chemical makeup of the different lens types. For all lenses, carbon, oxygen, and nitrogen were observed in varying quantities. In addition, fluorine was detected at the outermost surface region of comfilcon A (3.4%) and lotrafilcon A and B (<0.5%). The silicon content of the near-surface region analyzed varied among lens types, ranging from a low of 1.6% (lotrafilcon B) to a high of 16.5% (comfilcon A). In most instances, silicon enrichment at the outermost surface was observed, resulting from differences in lens formulation and design. Conclusions: Lenses differed most in their surface silicon concentration, with lotrafilcon B and delefilcon A exhibiting the lowest silicon contents and comfilcon A lens exhibiting the highest. Silicon has hydrophobic properties, which, when found at the surface, may influence the wettability of the contact lenses and their interaction with the tear film and ocular tissues. Higher surface silicon contents have been previously correlated with adverse effects, such as enhanced lipid uptake, thus underscoring the importance of monitoring their presence.